The 10th International Seminar of Veterinary Medicine Camelids in Algeria & Maghreb - Dib, Amira; Boukhechem, Said; Bougherara, Hithem; Bererhi, El-Hacene; Kaufman, Peter (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This book is a collection of articles focused on recent research covering a species which is emblematic of scientific and commercial interest-the dromedary. The dromedary economy and its sustainability are of a capital importance for the future development of humanity. This research highlights camel productions systems and rearing practices, camel biodiversity and genetics, camel breeding and feeding, dromedary pathologies, anatomy particularities in dromedary, therapeutic virtues of camel products, as well as the industry's contribution to food security.